2020
DOI: 10.3389/fimmu.2020.613194
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaco-Optogenetic Targeting of TRPC Activity Allows for Precise Control Over Mast Cell NFAT Signaling

Abstract: Canonical transient receptor potential (TRPC) channels are considered as elements of the immune cell Ca2+ handling machinery. We therefore hypothesized that TRPC photopharmacology may enable uniquely specific modulation of immune responses. Utilizing a recently established TRPC3/6/7 selective, photochromic benzimidazole agonist OptoBI-1, we set out to test this concept for mast cell NFAT signaling. RBL-2H3 mast cells were found to express TRPC3 and TRPC7 mRNA but lacked appreciable Ca2+/NFAT signaling in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The cyclic adenosine monophosphate (cAMP) signalling pathway, a well-known downstream mediator of MrgprB/X2, indirectly triggers Ca 2+ release from intracellular stores, which may not be sufficient to induce rapid MrgprB/X2-mediated Ca 2+ elevation. Recent studies have shown that transient receptor potential canonical (TRPC) channels may contribute to MrgprB2-mediated mast cell activation independently of the FcεRI pathway [ 58 , 59 ]. However, further mechanistic studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclic adenosine monophosphate (cAMP) signalling pathway, a well-known downstream mediator of MrgprB/X2, indirectly triggers Ca 2+ release from intracellular stores, which may not be sufficient to induce rapid MrgprB/X2-mediated Ca 2+ elevation. Recent studies have shown that transient receptor potential canonical (TRPC) channels may contribute to MrgprB2-mediated mast cell activation independently of the FcεRI pathway [ 58 , 59 ]. However, further mechanistic studies are required.…”
Section: Discussionmentioning
confidence: 99%